Portable solar stove - Hazken, S.; Aidarkhanov, D. (Nazarbayev University, 2013)
The project uses Fresnel lens to concentrate the sunlight as it has more light and is more compact than reflectors. Fresnel solar cookers can heat foodstuff up to oil boiling temperatures, so it can cook more kind of foods. The lens concentrates light at the bottom of the cooking vessel, and the light path lies within the frame of the cooker. This makes it safer than parabolic concentrators. The last advantage is the modular and compact design which makes the whole device easy to transport where it may be necessary – outdoor trips, camping, or remote working fields.
Keywords: first research week; solar energy; portable solar cooker